PENILAIAN KEPUASAN PENGGUNA TERHADAP ATRIBUT PRODUK DENGAN MENGGUNAKAN MODEL KANO; STUDI KASUS DESAIN INKUBATOR BAYI - Tarigan, Ukurta; Ginting, Rosnani (Jurnal Sistem Teknik Industri, 2018)
A Newborns need special attention because it takes time to adapt to the outside world. In accordance with the standard post-neonatal procedures, newborns should be incorporated into the incubator within a certain period of time according to the infant's health level. Infant incubator as a medical device used to care for newborns, often get complaints from doctors and child nurses. The complaint indicates consumer dissatisfaction with infant incubator products in the hospital. Broadly speaking, complaints against infant incubators lie in inappropriate designs. To overcome these complaints the researchers apply the method of Kano to determine the satisfaction frome every technical characteristics. Through the mapping can be seen that from the seven attributes that become the question, there are two attributes that are in the category of Attractive namely "Additional Functions on Infant Incubator the Place Tube Oxygen" and "Size Door Holes is 15 cm". There is one attribute that is in the One Dimensional category that is "Infant Incubator Price Rp 10.000.000". While the four attributes are in the category Must be "Infant Incubator Dimension 70 cm x 50 cm x 40 cm", "The distance of the floor from the base of the compartment 100 cm", "Compartment infant incubator materials are Acrylic" and "The position of the controller on the infant incubator is in top right side ".